Pratiche di stesura della tesi di laurea in italiano LS - Załęska , Maria (Studia Romanica Posnaniensia, 2022)
In the Italian academic discourse research, Master’s degree theses used to be studied mainly from the perspective of linguistic competencies of their authors. However, strictly linguistic skills are not the only challenge for undergraduate, who must also convey intellectual content in appropriate discursive and rhetorical forms. The paper explores the patterns of a peculiar form of “collaborative writing”, i.e. the cooperation between the thesis supervisor and the student. Using the example of Master’s theses in lin- guistics, written in Italian as a foreign language, three basic didactic approaches are discussed in the paper. In the didactics of content the supervisors emphasize knowledge, i.e. linguistic concepts expected to be applied in a Master’s thesis. In the didactics of forms, the supervisors focus on the linguistic code, that is, on grammatical and lexical correctness of the Master’s thesis. In the didactics of forms of content the supervisors use regularities observed in academic discourse, such as genre and rhetorical structures, as valuable teaching resources likely to help students develop metacommunicative awareness.